Theoretical basis for reasonable population distribution in Tho Chu archipelago - Huong, Le Van; Khanh, Nguyen Ngoc; Nhung, Nguyen Thu; Hoang, Phi Thi Thu; Hai, Pham Hoang (Vietnam Journal of Marine Science and Technology, 2019)
Tho Chu archipelago is one of administrative units of Kien Giang province, Hon Nhan- one of its islands - is selected to become A1 base point of baseline for Vietnam territorial waters. If Tho Chau district is established, it will contribute to identifying sovereignty of Vietnam Southwest sea area following the United Nations Convention on the Law of the Sea, creating favourable conditions for islands’ socio-economic development, developing culture, enhancing effects of administration work and life quality of population in this island, firmly protecting sea border, securing island and sea sovereignty… However, the establishment of Tho Chu district appears in the context of streamlining administrative apparatus and limitation of capital for infrastructure construction in district level. This article focuses on the analysis of some factors affecting a reasonable population distribution in order to meet the requirement of building the Tho Chu into a district-level administrative unit in Kien Giang province